Pre-harvest microbial Interventions: Impact on disease prevention, fermentation dynamics, and wine aroma in grape cultivation - Yijun Zhang; Xinglu Duan; Xiaohua Ma; Shengyun Lv; Yanlin Liu; Xixi Zhao (Current Research in Food Science, 2025)
Microbial communities play a critical role in determining both fruit health and fermentation outcomes along the grape-to-wine continuum, yet their diversity dynamics within holistic production systems remain poorly understood. In this study, we investigated the impact of pre-harvest interventions—specifically the application of Saccharomyces cerevisiae NX2320, Trichoderma harzianum, and fludioxonil—on microbial community trajectories and wine aroma profiles during spontaneous fermentation. We demonstrated that all treatments significantly suppressed grape pathogens compared to untreated controls, while simultaneously restructuring the microbial communities in grape juice. This restructuring influenced fermentation outcomes, leading to distinct volatile compound profiles in the final wines. Notably, the S. cerevisiae-treated group exhibited rapid dominance of Saccharomyces (initial abundance: 89.96 %), which accelerated ethanol production and elevated key esters such as isobutyl acetate and 1-butanol-3-methyl-acetate. These changes collectively enhanced fruity notes in the wines. Furthermore, fungal diversity inversely correlated with fermentation progression, reinforcing the role of Saccharomyces in simplifying the microbial ecosystem. Crucially, early microbial modulation (pre-fermentation) proved to be a pivotal factor in determining the sensory attributes of the final wines, with the timing and type of intervention significantly influencing the variability of volatile compounds. These findings establish a causal relationship between agricultural microbiome management and oenological quality, offering actionable strategies for optimizing wine microbiota engineering and achieving desired aromatic characteristics.